IMPROVISED THE PROGRESSION OF THE SONG BALONKU BY A.T MAHMUD: JUDGING FROM MODERN PIANO PLAYING TECHNIQUES - Andre Alfandi Mendrofa; Junita Batubara (Sahabat Publikasi, 2023)
This article discusses the improvisation of progressions and modern piano playing techniques in the song Balonku. The song Balonku is the work of A.T Mahmud (alm.) which was created in 1963. He is a maestro of Indonesian children's songs. He has composed many very educational children's songs. The owner of the full name Abdullah Totong Mahmud often appears on the Ayo Singnya program on the Indonesian television station, TVRI. This Indonesian culturalist has even been given the Parama Dharma Cultural Star Honor for his services in popularizing children's songs. My Balloon Song has the meaning of educating to learn from a loss and take good care of it so as not to lose again. The method approach used is descriptive qualitative by collecting data through youtube observation (https://youtu.be/VfPX6VGsa9g), literature studies, and documentation. The results of this research will show the work in a performance form of presentation of the song.